Implementation of Independent Curriculum Policy in Facing the Society 5.0 Era - Julizar Idris; Jumanah Jumanah; Ira Rahmawati; Marlina Marlina; Nurlinda Nurlinda (Program Pascasarjana Universitas Negeri Makassar, 2024)
The rapid development of technology in the era of society 5.0 is characterized by the rapid pace of information technology, this also makes various challenges appear in various aspects, one of which is education. The functions and objectives of National Education are none other than to develop capabilities and form distinguished national character and civilization in the context of educating the nation's life. In the education system in Indonesia. This research was conducted with a qualitative approach, through literature studies. Data collection was carried out by tracing various sources of literature or literature in the form of RI Minister of Education and Culture Regulation Number: 262/M/2022, journals, and other documents related to the independent curriculum. The independent learning curriculum is presented as an answer to the occurrence of a comprehensive transformation in all aspects, especially the demands of human resources who are able to compete and adapt. The implementation of the independent curriculum in the era of society 5.0 for 12 years of compulsory education has been implemented since February 2022 by the MENDIKBUDRISTEK as one of the independent learning programs to improve the quality of learning. Monotonous learning is a barrier for students to demonstrate their abilities and competencies. The pattern of life that is happening is increasingly dynamic as if there are no limits, this is proven by the development of the world of technology which is growing rapidly. Therefore, education must be able to keep up with the dynamics of the times. In its application, the Merdeka curriculum must also be adapted to the conditions and characteristics of each school, so as to maximize existing potential. In this case, schools must be able to identify the needs and challenges faced, and develop appropriate strategies to overcome them. Thus, it is hoped that the learning process in schools can run well and produce quality output.